2020
DOI: 10.1007/s00464-020-08126-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic papillectomy; a retrospective international multicenter cohort study with long-term follow-up

Abstract: Background Endoscopic papillectomy (EP) is considered a relatively safe and minimally invasive treatment for papillary adenomas. In the literature a significant risk for local recurrence is described. The aim of this study was to evaluate long-term recurrence rates and time-to-recurrence. Additionally, risk factors for recurrence, malignancy and adverse events were studied. Methods This is a retrospective study in consecutive patients with papillary adenomas who underwent EP in two tertiary referral hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Although generally considered safe, EP is not without risks, with serious adverse events occurring in 15-35% of patients and recurrence in up to 20% during surveillance. [3][4][5][6][7]26 It is therefore incumbent on those managing these patients to further refine and optimize the EP procedure to mitigate against these adverse events. However, high-level scientific knowledge to guide this process is largely absent because papillary adenomas are uncommon, and thus large prospective multicenter or randomized controlled studies have not been executed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although generally considered safe, EP is not without risks, with serious adverse events occurring in 15-35% of patients and recurrence in up to 20% during surveillance. [3][4][5][6][7]26 It is therefore incumbent on those managing these patients to further refine and optimize the EP procedure to mitigate against these adverse events. However, high-level scientific knowledge to guide this process is largely absent because papillary adenomas are uncommon, and thus large prospective multicenter or randomized controlled studies have not been executed.…”
Section: Discussionmentioning
confidence: 99%
“…6,24,25 Furthermore, a recent series of patients who underwent EP showed that in only half of the lesions in which the resection specimen showed adenocarcinoma, malignancy was already suspected based on the endoscopic appearance, further questioning the accuracy of endoscopic assessment. 26 Advanced imaging techniques such as narrow-band imaging and chromoendoscopy have proven to be a valuable addition to white-light imaging in the diagnosis of colorectal lesions. 27 However, the possible benefit of narrowband imaging in the assessment of papillary lesions is only described in a small case series.…”
Section: Recommendation Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Recurrence remains the Achilles heel in endoscopic papillectomy due to the complex- related anatomy. 2 Cold snare papillectomy, albeit not systematically studied, represents a novel principle and may have a role in selected lesions and clinical settings. 3 …”
Section: Linical R Eportmentioning
confidence: 99%